DQB1*06:02-Associated Pathogenic Anti-Myelin Autoimmunity in Multiple Sclerosis-Like Disease: Potential Function of DQB1*06:02 as a Disease-Predisposing Allele - Kaushansky, Nathali; Ben-Nun, Avraham (Frontiers in Oncology, 2014)
Susceptibility to multiple sclerosis (MS) has been linked mainly to the HLA-DRB1 locus, with the HLA-DR15 haplotype (DRB1*1501-DQA1*0102-DQB1*0602-DRB5*0101) dominating MS risk in Caucasians. Although genes in the HLA-II region, particularly DRB1*1501, DQA1*0102-DQB1*0602, are in tight linkage disequilibrium, genome-wide-association, and gene candidate studies identified the DRB1*15:01 allele as the primary risk factor in MS. Many genetic and immune-functional studies have indicated DRB1*15:01 as a primary risk factor in MS, while only some functional studies suggested a disease-modifying role for the DRB5*01 or DQB1*06 alleles. In this respect, the susceptibility of DRB1*15:01-transgenic (Tg) mice to myelin basic protein- or myelin oligodendrocyte glycoprotein-induced MS-like disease is consistent with primary contribution of DRB1*15:01 to HLA-DR15+ MS. The studies summarized here show that susceptibility to MS-like disease, induced in HLA-“humanized” mice by myelin oligodendrocytic basic protein or by the proteolipid protein, one of the most prominent encephalitogenic target antigens implicated in human MS, is determined by DQB1*06:02, rather than by the DRB1*15:01 allele. These findings not only offer a rationale for a potential role for DQB1*06:02 in predisposing susceptibility to MS, but also suggest a more complex and differential functional role for HLA-DR15 alleles, depending on the primary target myelin antigen. However, the conflict between these findings in HLA-Tg mice and the extensive genome-wide-association studies, which could not detect any significant effect from the DQB1*06:02 allele on MS risk, is rather puzzling. Functional analysis of MS PBLs for DQB1*06:02-associated anti-myelin autoimmunity may indicate whether or not DQB1*06:02 is associated with MS pathogenesis.